(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Food packaging industry mainlyuses petroleum based packaging materials, which are non- biodegradable, even if they are bio degradable they break down into smaller molecules, which are not harmless to the ecology. These packaging materials, once discarded, sit in the landfills for approximately 1000 years contributing to the harmful effects to plant and animal lives because chemicals leach into the soil. These chemicals ultimately seep into the ground water and effect health as agricultural and animal produce get affected. In addition to this, harmful chemicals leach into the food while the wrapper covers the fresh or hot food. Researchers are trying to produce zero waste packaging, since past many years. Animal produce based edible gelatin packaging and plant produce based rice paper packaging can be made at home, but the need of the times is mass production of both animals based and plant based packaging materials, which cause no pollution to the environment and ecosystem. The present paper discusses some progress made in this field recently.